Dooleys Geheimnis - Brooks, Bruce,Neckenauer, Ulla,Mönster, Jub (Maier, 1993)
Afraid that his beloved grandfather will die after suffering a heart attack, a nine-year-old boy agrees to join ten-year-old Dooley in performing a mysterious ritual called soul switching.
Keywords: Kinderbuch; Death; German language materials; Grandfathers; Geistheilung; Großvater